2017
DOI: 10.1186/s12879-017-2215-1
|View full text |Cite
|
Sign up to set email alerts
|

Study on age-dependent pre-existing 2009 pandemic influenza virus T and B cell responses from Chinese population

Abstract: BackgroundThe outbreak of the 2009 H1N1 influenza pandemic (H1N1pdm) affected thousands of people in Mexico and the United States, and spread rapidly throughout the world from April 2009 to July 2010. To explore the age-specific prevalence of seroprotection against H1N1pdm infection, we estimated pre-existing humoral and cellular immunities of residents in Northern China against H1N1pdm and seasonal H1N1 virus in an age-dependent manner.MethodsAnonymous serum samples were collected from 1425 to 1434 adult heal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…This finding also corroborates with the study of Jin Lv et. al, 2017 [7] reporting higher prevalence in elder age group which was not exposed previously. In our study it was observed that infection rate was higher among male individuals (50.6%) than females (49.3%) though the difference is not significant.…”
Section: Discussionmentioning
confidence: 99%
“…This finding also corroborates with the study of Jin Lv et. al, 2017 [7] reporting higher prevalence in elder age group which was not exposed previously. In our study it was observed that infection rate was higher among male individuals (50.6%) than females (49.3%) though the difference is not significant.…”
Section: Discussionmentioning
confidence: 99%
“…Previous Interestingly, a systems analysis suggested that the immune system of an individual is defined by specific exposure frequency, that an individual encounters in their lifetime [165]. From the experience during the last pandemic in 2009, older people who were born in 1940's had less severe infection due to the presence of pre-existing crossreactive anti pdm2009 antibody [166,167]. Several studies show that the stalk specific broadly neutralizing antibodies increase with age due to previous experience with divergent influenza viruses [168,169].…”
Section: Targeting Influenza Vaccines By Age or Gendermentioning
confidence: 99%
“…This finding corroborates with the study by Dwibedi et al 1 from Odisha from 2009 to 2017, where 29.7% of the cases were in the age group of 51 to 60 years followed by 22.7% in the age group of 31 to 40 years. Also, a study of Lv J et al 16 in 2017 reported higher prevalence in older age group, perhaps as this group was not exposed previously. However, studies from Queensland, 17 Saudi Arabia, 18 and the United States 19 showed cases to be more common in young age from 10 to 17 years.…”
Section: Discussionmentioning
confidence: 87%
“…the age group of 51 to 60 years followed by 22.7% in the age group of 31 to 40 years. Also, a study of Lv J et al16 in 2017 reported higher prevalence in older age group, perhaps as this group was not exposed previously. However, studies from Queensland,17 …”
mentioning
confidence: 87%